The oceans : - Groves, Donald G. (Wiley, 1989)
Facts and technical data on the world’s oceans… The Oceans This guide to the most powerful and mysterious natural force is written for everyone who loves the ocean. The coverage is wide-ranging and in-depth, and the presentation underscores how important the oceans are to the inhabitants of this planet, and how their resources must be protected and best utilized for the welfare of humanity. In a lively, easy-to-read, question-and-answer format, The Oceans offers insights, facts and figures in answer to over 100 questions about the ocean.